The effect of printing parameters on the properties of 17-4 PH stainless steel fabricated by material extrusion additive manufacturing - SEENSATTAYAWONG, Phanuphak; SUWANPREECHA, Chanun; BOONLERT, Natthanicha; SONGKUEA, Sukrit; MANONUKUL, Anchalee (Journal of Metals, Materials and Minerals, 2024)
The 17-4PH stainless steel filament was characterised and utilised to study the effect of printing parameters, i.e. printing temperature, layer thickness, infill pattern and extrusion multiplier on the physical properties. The as-printed and as-sintered internal structures were analysed. The results showed that the as-printed density increases with increasing printing temperature and extrusion multiplier and decreasing layer thickness. The use of the line infill pattern also provided slightly higher as-printed density than the concentric infill pattern due to the low fraction of void between deposited paths. After sintering, the trace of these voids can be observed together with smaller-size residual pores from the spaces between powders, which is the nature of the pressureless sintering process. The microstructure of the as-sintered specimens was similar to the typical microstructure of the 17-4PH alloy fabricated by metal injection moulding process, which contains delta ferrite, martensite and Si-rich phases. In additions, the internal void generated during debinding and sintering results in unexpectedly low tensile properties and results in the difference in tensile properties between the concentric and line infill patterns.